Effects of Mathematics Learning Activities Using Heuristics Thinking with Visual Learning Strategies on Mathematical Communication Ability of Lower Secondary Students - Konglawan, Nanthiya; Thamsuan, Jongkol (An Online Journal of Education, 2024)
The purposes of this research were: 1) to compare the mathematical communication ability of students before and after learning using heuristics thinking with visual learning strategies, 2) to compare the mathematical communication ability of students after learning using heuristics thinking with visual learning strategies to the criteria score 60%, and 3) to study the development of the mathematical communication ability of the students taught using heuristics thinking with visual learning strategies. The subjects were 39 seventh grade students in an extra-large school under Secondary Educational Service Area Office 27, which were selected by purposive sampling. The instruments used for research were 15 lesson plans and a mathematical communication ability test. The data were analyzed using arithmetic mean, standard deviation, percentage, t-test, and content analysis. The results of the research reveal that 1) the mathematical communication ability of the students after learning using heuristics thinking with visual learning strategies were higher than those of the students before being taught using heuristics thinking with visual learning strategies at the .05 level of significance, 2) the mathematical communication ability of the students after learning using heuristics thinking with visual learning strategies were not higher than 60% at the .05 level of significance, and 3) the mathematical communication ability of the students learning using heuristics thinking with visual learning strategies improved.